PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI BERBASIS ETNOPEDAGOGI TEMA 8 SUBTEMA 1 DI KELAS V SD NEGERI 2 PLIKEN - Hidayatul Ngilmiah; Aji Heru Muslim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
A teacher can create a learning process so that there is reciprocal interection between teachers and stundents and become more effective and efficient by using learning media. One of the learning media innovations that are fun and educational for use in learning is the ethnopedagogy-based monopoly media. This study to develop learning media, test the feasibility of the media and find out the responses of teacher and students. This study uses the ADDIE model research and development (R & D) research method in Robert Maribe Branch (2009). The results of the validation of monopoly learning media products based on ethnopedagogy in this study obtained an average score of 86% including very valid criteria. The results of the teacher’s and stundents’ responses received a positive response with the acquisition of an average score of the teacher responses, which was 87% including very goog criteria and the average score of student responses was 95% including very interesting criteria. Based on the analysis of validator questionnaires, teacher and student responses, the ethnopedagogy-based monopoly learning media on theme 8 sub-theme 1 has met the criteria for use in the classroom learning process.